2008
DOI: 10.1016/j.yexcr.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial translocation of α-synuclein is promoted by intracellular acidification

Abstract: Mitochondrial dysfunction plays a central role in the selective vulnerability of dopaminergic neurons in Parkinson's disease (PD) and is influenced by both environmental and genetic factors. Expression of the PD protein α-synuclein or its familial mutants often sensitizes neurons to oxidative stress and to damage by mitochondrial toxins. This effect is thought to be indirect, since little evidence physically linking α-synuclein to mitochondria has been reported. Here, we show that the distribution of α-synucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(180 citation statements)
references
References 69 publications
(80 reference statements)
4
171
1
4
Order By: Relevance
“…As described before, oxidative damage to alphaͲsyn affects its aggregation Ͳ an effect that partially explains the cellular toxicity of the protein. AlphaͲsyn contains an NͲterminal mitochondrialͲtargeting sequence [181], and cytosol acidification or alphaͲsyn overexpression can lead the protein to localize to mitochondria [182,183], resulting in complex I impairment and increased ROS production [181], increased protein tyrosine nitration and decreased mitochondrial transmembrane potential [184]. In addition, it was shown that human embryonic kidney cells that overexpress alphaͲsyn, show enhanced susceptibility to cell death and have lower ATP levels compared to control cells [183].…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
“…As described before, oxidative damage to alphaͲsyn affects its aggregation Ͳ an effect that partially explains the cellular toxicity of the protein. AlphaͲsyn contains an NͲterminal mitochondrialͲtargeting sequence [181], and cytosol acidification or alphaͲsyn overexpression can lead the protein to localize to mitochondria [182,183], resulting in complex I impairment and increased ROS production [181], increased protein tyrosine nitration and decreased mitochondrial transmembrane potential [184]. In addition, it was shown that human embryonic kidney cells that overexpress alphaͲsyn, show enhanced susceptibility to cell death and have lower ATP levels compared to control cells [183].…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
“…Low pH is furthermore associated with PD through both the exosomes via the lysosomal pathway 42 and oxidative or metabolic stress in mitochondria. 43 The contrast in NR is determined by the differences in the scattering length density (SLD) values for the various sample components. Hydrogen and deuterium have markedly different SLD values, and with a change in the degree of deuteration of lipids, protein, and solvent, the contribution from the different components to neutron scattering of a sample can be matched so that the scattering from a specific part, region, or component of interest is highlighted.…”
mentioning
confidence: 99%
“…The gene coding for -synuclein has a terminal sequence with mitochondrial target [23]. Cytosol acidifi cation or overexpression of -synuclein can lead to accumulation of this protein in mitochondria [24].…”
Section: Risk Level Environmental Agentmentioning
confidence: 99%